The Emperor cult in Moesia Inferior and the problem of romanisation - Gočeva, Zlatozara (Balcanica Posnaniensia. Acta et studia, 1990)
The article analyzes the problem of the imperial cult in the province of Lower Moesia and its significance for the process of romanization. The problem is significant for studies on the relationship between state religion and cultural transformations in Roman provinces. The aim of the work is to examine the spread of the ruler cult and its functioning in various urban centers. The author uses analysis of epigraphic and numismatic material. The most important results indicate that the imperial cult developed mainly in cities and military centers, where the presence of the army favored romanization. At the same time, its forms were regionally diverse and often combined with local religious traditions. The analysis also shows connections between the imperial cult and the cult of Jupiter and the Capitoline triad. The conclusion is that the ruler cult was an important tool of integration of the provinces with the empire, although its impact depended on local conditions.